2019
DOI: 10.1002/jbm.a.36691
|View full text |Cite
|
Sign up to set email alerts
|

Safety and biocompatibility of injectable vaccine adjuvants composed of thermogelling block copolymer gels

Abstract: Injectable thermogelling polymers have been recently investigated as novel adjuvants and delivery systems for next generation vaccines. As research into natural and synthetic biocompatible polymers progresses, the safety and biocompatibility of these compounds is of paramount importance. We have developed cationic pentablock copolymer (PBC) vaccine adjuvants based on Pluronic F127, a thermogelling triblock copolymer that has been approved by the FDA for multiple applications, and methacrylated poly(diethyl ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Rapid glycolytic activity as demonstrated by the TLR agonists in extracellular flux analysis has been reported to contribute to inflammation . In a separate study using cathepsin activity, we have demonstrated that micelles do not induce inflammation at the site of injection . Combined with the glycolytic activity of the micelles demonstrated in this work (Figure ), this suggests that a potential benefit of micelle adjuvants would be to avoid adverse inflammatory reactions.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Rapid glycolytic activity as demonstrated by the TLR agonists in extracellular flux analysis has been reported to contribute to inflammation . In a separate study using cathepsin activity, we have demonstrated that micelles do not induce inflammation at the site of injection . Combined with the glycolytic activity of the micelles demonstrated in this work (Figure ), this suggests that a potential benefit of micelle adjuvants would be to avoid adverse inflammatory reactions.…”
Section: Methodssupporting
confidence: 63%
“…In this study, we prepared low concentration PBCs in aqueous solutions to form micelles without gelation that still enhanced antibody responses. This also eliminates any potential inflammatory responses associated with the high polymer concentrations needed to form gels 31 . However, little is known about the mechanism of action of PBC micelle adjuvants; how they interact with innate immune cells; and how these interactions lead to the induction of effective adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of PBCs, like those used in this study, form hydrogels composed of micellar structures. Hydrogels comprised of 4.1 wt% PBC, and 5.9 wt% Pluronic F127 were prepared in PBS (0.05 M, pH 7.2) at 4 °C based on previous safety studies . rH3 3 protein was added to obtain a final concentration of 4 mg/mL in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Narsimhan and co-workers, developed grafted cationic pentablock copolymers based on Pluronic F127 and poly(diethylaminoethylmethacrylate) (PDEAEM) blocks for sustained vaccine delivery. Following subcutaneous injection, these thermogelling polymers formed safe hydrogel depots in situ without any reactogenicity [73] and stimulated strong antigen-specific antibody responses when hydrogels were loaded with the OVA antigen [74].…”
Section: Temperature Responsive In Situ-forming Hydrogelsmentioning
confidence: 99%